Gestores de paz: estrategia pedagógica para la mitigación del conflicto escolar y la promoción de cultura ciudadana (2019)
One of the most important aspects of our society is the education of children in their integral formation, for which, in the school environment, both agreements and disagreements of the actors in the scenarios of peaceful coexistence must prevail, That is why the construct is mobilized in the promotion of strategies aimed at mitigating school conflicts, but at the same time, working together with the educational community in the dimension of citizen culture based on pedagogical strategies with a view to strengthening coexistence in The target institution. Likewise, it seeks to promote a good school environment through the practice of tolerance, responsibility, participation and democracy; creating better students and demonstrating the principle of justice; Therefore, the school must be "Space of peace", where the creation of democratic, axiological and socio-emotional processes in the peaceful regulation of conflicts is visualized in groups.